How climate change adaptation projects can advance gender equality and progress toward SDG 5 - Some, Shreya; Roy, Joyashree (CGIAR GENDER Impact Platform, 2022)
"Key messages - Existing societal dynamics, including women’s lack of access to technology and their increasing labor burden due to forced migration, are some of the key reasons behind gender inequality in climate change adaptation projects. - Embedding gender considerations and facilitating women’s participation in design and implementation of climate adaptation projects—along with inclusive policies, training, information access, planning and monitoring—is a must to avoid gender inequality. - Evidence is clear: conscious efforts are essential to integrate local, Indigenous, intergenerational knowledge and institutions in existing, otherwise biased, formal scientific and institutional arrangements. Women play important roles in supporting, teaching and adapting traditional knowledge to climate change adaptive actions. "